Esotericism in Islamic Thought as a Political Perspective - Ikhwan al-Safa as a model - Dr. Hussein Abbas Hussein, (The college of law and political science journal, 2023)
Esotericism in Islamic Thought as a Political Perspective - Ikhwan al-Safa as a model